2021
DOI: 10.1073/pnas.2105288118
|View full text |Cite
|
Sign up to set email alerts
|

Tradeoffs for a viral mutant with enhanced replication speed

Abstract: RNA viruses exist as genetically heterogeneous populations due to high mutation rates, and many of these mutations reduce fitness and/or replication speed. However, it is unknown whether mutations can increase replication speed of a virus already well adapted to replication in cultured cells. By sequentially passaging coxsackievirus B3 in cultured cells and collecting the very earliest progeny, we selected for increased replication speed. We found that a single mutation in a viral capsid protein, VP1-F106L, wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…In previous selections with other RNA viruses, adaptation to one environment can have fitness trade-offs that reduce fitness in other environments [32, 33, 45, 46]. In our study we found that all the plaque-purified viruses from the HeLa-passaged lineages had decreased replication in BV2 cells.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In previous selections with other RNA viruses, adaptation to one environment can have fitness trade-offs that reduce fitness in other environments [32, 33, 45, 46]. In our study we found that all the plaque-purified viruses from the HeLa-passaged lineages had decreased replication in BV2 cells.…”
Section: Discussionsupporting
confidence: 55%
“…Previously our lab and others have used viral passaging in restrictive environments to select for RNA viruses with various traits such as faster replication, drug resistance, increased thermostability, and altered plaque size [32][33][34][35]. Most of these viral passaging studies have resulted in a small number of mutations and often the phenotype of interest can be traced back to a single mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar vaccine candidates with deletions in accessory genome regions have been developed for various pathogenic viruses, including delta-6K and delta-5 (nsP3) mutants in Chikungunya virus 30 , 30 nucleotide 3′ UTR deletion in Dengue virus 31 , recently reported SARS-CoV-2 deletions in the multi-basic cleavage sites of spike protein 32 , or combination of several known attenuation approaches that can provide a safer strategy to prevent reversion to virulence 33 . Besides attenuation in vivo , trade-offs for enhanced cell culture replication may result in reduced particle stability 34 . Taken together, the identification of the attenuation region in the MLB group of astroviruses brings us a step forward in understanding the mechanisms responsible for virulence in this group of viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the required function of caspases, the astrovirus release is described as an unclassified nonlytic process 8 . In some astroviruses, the structural polyprotein is cleaved by trypsin resulting in the formation of 3ʹ truncated (25)(26)(27)(28)(29)(30)(31)(32)(33)(34) proteins. Maturation of the astrovirus capsid protein is a very dynamic process, transforming the virus from a non-infectious intracellular form (VP90) to a primed extracellular form (VP70), and finally generating an icosahedral infectious mature virion (VP34/27/25).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some variations that occurred on the virulent variant (CB4-V) of coxsackievirus B4 increased the antigenicity, potentially inducing more severe disease [ 36 ]. The VP1-F106L mutation of coxsackievirus B3 has been found to produce a rapidly replicating phenotype, accelerating the release of viral genome, whereas reducing the stability of viral capsid [ 37 ]. In addition, previous studies verified that KREMEN1 was a host entry receptor for CV-A12 [ 38 , 39 ]; however, many studies focused on the host binding and entry mechanism of EV-A71 and other common enterovirus serotypes.…”
Section: Discussionmentioning
confidence: 99%